Riverine microplastic contamination in southwest Germany: A large-scale survey - Schrank, Isabella; Löder, Martin G. J.; Imhof, Hannes K.; Moses, Sonya R.; Heß, Maren; Schwaiger, Julia; Laforsch, Christian (Frontiers in Earth Science, 2022)
Microplastic (MP) contamination of freshwater ecosystems is still in the focus of research and public attention, as aquatic environments have a high ecological, economic, and recreational value. We now know that rivers do not only function as pathways of MPs into oceans but may also act as temporary MP sinks. However, due to methodological differences, the comparability of studies on MP contamination of rivers is still limited. To compare MP contamination between different river systems, to analyze if there is a constant increase in MP contamination from the upper to the lower course of the river, and to investigate if there are distinct MP distribution patterns, we set up a large-scale survey. We chose two large river systems, the Rhine and Danube catchments with their tributaries and sampled 23 rivers of different sizes at 53 sampling locations in southwest Germany. Surface water sampling, sample processing, and analysis were performed with the same methodology to obtain comparable results on MP number, polymer type, and particle’s size and shape. Fully quantitative data were generated down to 300 µm by using a manta trawl net with a 300-µm mesh size for sampling. Nevertheless, we also included the non-quantitative sampled fraction of particles down to a size of 20 µm in our FTIR analysis after plastic-friendly sample purification by enzymatic oxidative treatment. Plastic concentrations recorded in surface water at the sampling locations ranged from 0.7 to 354.9 particles/m³. Concerning all samples, the number of particles increased toward lower size classes (61.0 ± 34.2% below 300 µm), and fragments were the prevailing shape (90.7 ± 13.6%). Polyethylene (49.2 ± 25.9%) and polypropylene (33.2 ± 22.6%) were the most frequent polymer types. Our survey did not reveal distinct MP distribution patterns or a constant increase of MP abundance within river courses in the investigated river systems. Next, to provide a large-scale dataset of microplastic contamination in surface waters of southwest Germany, our study shows that a representative sampling of MPs in rivers is challenging. MP particles are not homogeneously distributed in rivers, and this indicates that spatial and temporal changes in MP abundance should always be considered in MP monitoring approaches.